PELATIHAN PEMBUATAN IKLAN PEMASARAN PRODUK PROMOSI MENGGUNAKAN APLIKASI VOICE MAKER PENGISI AUDIOTEXT TO SPEECH (TTS) DI SMK BM BUDI AGUNG MEDAN - Siregar, Elida Tuti; Alfina, Ommi; Ambarita, Wisesa Panca Praja Damanik (Jurnal Pengabdian Pada Masyarakat METHABDI, 2023)
Product promotion is an activity of introducing products, persuading, reminding and influencing the public so that potential buyers want to buy the goods and services offered. Advertising in the form of communication that has the intention of conveying information about the products offered with global marketing communications and e-marketing using a combination of graphics, animation and sound. This training is aimed at students at private schools in the city of Medan, SMK Budi Agung Class XII, majoring in marketing, in the form of multimedia practicum training using Macromedia Flash, making product advertisement animations and advertising voiceovers using the Voice maker Free Text to Speech (TTS) application. This training is a higher education tridharma each semester carrying out community service as a routine each semester.